Preference for shelter and additional heat in horses exposed to Nordic winter conditions. (10th December 2015) - Jørgensen, G. H. M.; Aanensen, L.; Mejdell, C. M.; Bøe, K. E.
Summary: Reasons for performing study: Horses may adapt to a wide range of temperatures and weather conditions. Owners often interfere with this natural thermoregulation ability by clipping and use of blankets. Objectives: To investigate the effects of different winter weather conditions on shelter seeking behaviour of horses and their preference for additional heat. Study design: Observational study in various environments. Methods: Mature horses (n = 22) were given a free choice test between staying outdoors, going into a heated shelter compartment or into a nonheated shelter compartment. Horse location and behaviour was scored using instantaneous sampling every minute for 1 h. Each horse was tested once per day and weather factors were continuously recorded by a local weather station. Results: The weather conditions influenced time spent outdoors, ranging from 52% (of all observations) on days with mild temperatures, wind and rain to 88% on days with <0°C and dry weather. Shivering was only observed during mild temperatures and rain/sleet. Small Warmblood horses were observed to select outdoors less (34% of all observations) than small Coldblood horses (80%). We found significant correlations between hair coat sample weight and number of observations outdoors (ρ = 0.23; P = 0.004). Conclusions: Horses selected shelters the most on days with precipitation and horses changed from a nonheated compartment to a heated compartment as weather changed from calm and dry to wet and windy. Horse breed category affected the use of shelter and body condition score and hair coat weight were associated with voluntary shelter selection.